Analisis Harga Pokok Produksi Dengan Metode Full Costing Terhadap Penetapan Harga Jual Pada Pabrik Kerupuk Malarat Di Kabupaten Karawang - Dela Rosdiana; Neni Triana; Thomas Nadeak (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
With the increasing growth conditions of food companies, it is important for companies to set appropriate prices to be able to compete with other companies. Therefore, the calculation of product prices must be done correctly and precisely to get maximum profit. Likewise by the malarat cracker factory in Karawang, which currently still uses estimates in determining the cost of goods produced. This study aims to attain an understanding of comprehensive production cost computation through the implementation of the full costing method. The data employed in this research emanates from corporate information acquired through data collection processes and document analysis. The employed method of data analysis is characterized as quantitative-descriptive. The outcomes of the study reveal the existence of disparities in the production cost estimates formulated by the company through the utilization of the full costing method. This circumstance arises due to the company's calculations failing to encompass the entirety of cost factors utilized within the company's operations. Keywords: Cost of goods produced, full costing method.